Optimization of Cooperative Production Function in The Philippines And Indonesia - Pratiknyo, Yanto Sidik; Bangun, Wilson; Hidayah, Zainur; Kambara, Roni (Asean International Journal of Business, 2023)
Purpose – The study aims to identify production function equation between labour and capital also optimal cost of labour and capital of the cooperatives. In order to raise the level of this research to be international, this study compares two countries, namely the Philippines and Indonesia by applying performances of cooperatives in both countries. Methodology/approach – Cobb Douglass production function equation of labour and capital is applied in this research. Optimal cost using partial differential equation also used between cost of wage of labour and cost of capital. Cooperatives in 15 regions in Philippines and 33 provinces in Indonesia were the object of the research Findings – Philippines has an increasing scale of return because the value of the constant is greater than one, on the other hand Indonesia has a declining scale of return. However, the two countries have in common that capital is correlated with cooperative output, while labour is not correlated with output significantly. Novelty/value – This study highlights the important of the use of economic analytical of the capital and labour to the cooperatives in Philippines and Indonesia. Both   cooperatives have significant correlation between output and capital, but did not correlate significantly to labour.